Environmental pollution liability insurance and green innovation of enterprises: Incentive tools or self-interest means? - Ning, Jinhui; Yuan, Zeming; Shi, Fang; Yin, Shi (Frontiers in Environmental Science, 2023)
This paper, based on the list of enterprises insuring environmental pollution liability insurance (EPLI) as published by the Ministry of Ecology and Environment, explores the impact of EPLI on green innovation of enterprises. It is found that insuring EPLI can significantly improve the green innovation of enterprises. The effect path test shows that EPLI can promote the green innovation of enterprises by relaxing financing constraints and reducing agency costs. The test of heterogeneity scenario shows that compared with non-state-owned enterprises, non-heavily polluting enterprises, and enterprises in regions with lower intensity of environmental regulation, EPLI plays a stronger role in the promotion of green innovation of state-owned enterprises, heavily polluting enterprises and enterprises in regions with higher intensity of environmental regulation. In addition, it is found that the promotion effect of EPLI on green innovation is mainly reflected in the significant improvement of high-quality green innovation and the optimization of the structure of the green patent output. This paper affirms the positive role of EPLI on green operations of enterprises and provides empirical evidence that green insurance serves the development of green innovation of enterprises.